Actuators and transmission mechanisms in rehabilitation lower limb exoskeletons: A review - Ramli, Rizauddin; Aliman, Norazam; Amiri, Mohammad Soleimani (De Gruyter, 2024)
Research has shown that rehabilitation lower limb exoskeletons (RLLEs) are effective tools for improving recovery or regaining lower limb function. This device interacts with the limbs of patients. Thus, actuators and power transmission mechanisms are the key factors in determining smooth human‒machine interaction and comfort in physical therapy activities. A multitude of distinct technologies have been proposed. However, we questioned which consideration point in actuator selection and power transmission mechanisms are used for RLLE. A review of the technical characteristics and status of advanced RLLE designs is discussed. We review actuator selection for RLLE devices. Furthermore, the power transmission mechanisms over the years within each of the RLLE devices are presented. The development issues and possible research directions related to actuators and power transmission mechanisms are provided. Most RLLEs are still in the research phase, and only a few have been commercialized. The aim of this paper is to provide researchers with useful information for investigating technological progress and highlight the latest technological choices in RLLE development.